Differential Regulation of the Expression of the Two Thyrotropin Beta Subunit Paralogs by Salmon Pituitary Cells In Vitro - Fleming, Mitchell Stewart; Maugars, Gersende; Martin, Patrick; Dufour, Sylvie; Rousseau, Karine (Frontiers in Endocrinology, 2020)
We recently characterized two paralogs of the thyrotropin (TSH) beta subunit in Atlantic salmon, tshβa and tshβb, issued from teleost-specific whole genome duplication. The transcript expression of tshβb, but not of tshβa, peaks at the time of smoltification, which revealed a specific involvement of tshβb paralog in this metamorphic event. Tshβa and tshβb are expressed by distinct pituitary cells in salmon, likely related to TSH cells from the pars distalis and pars tuberalis, respectively, in mammals and birds. The present study aimed at investigating the neuroendocrine and endocrine factors potentially involved in the differential regulation of tshβa and tshβb paralogs, using primary cultures of Atlantic salmon pituitary cells. The effects of various neurohormones and endocrine factors potentially involved in the control of development, growth and metabolism were tested. Transcript levels of tshβa and tshβb were measured by qPCR, as well as those of growth hormone (gh), for comparison and validation. Corticotropin-releasing hormone (CRH) stimulated tshβa transcript levels in agreement with its potential role in the thyrotropic axis in teleosts, but had no effect on tshβb paralog, while it also stimulated gh transcript levels. Thyrotropin-releasing hormone (TRH) had no effect on neither tshβ paralogs nor gh. Somatostatin (SRIH) had no effects on both tshβ paralogs, while it exerted a canonical inhibitory effect on gh transcript levels. Thyroid hormones (triiodothyronine, T3 and thyroxine, T4) inhibited transcript levels of both tshβ paralogs, as well as gh, but with a much stronger effect on tshβa than on tshβb and gh. Conversely, cortisol had a stronger inhibitory effect on tshβb than tshβa, while no effect on gh. Remarkably, insulin-like growth factor 1 (IGF1) dose-dependently stimulated tshβb transcript levels, while it had no effect on tshβa, and a classical inhibitory effect on gh. This study provides the first data on the neuroendocrine factors involved in the differential regulation of the expression of the two tshβ paralogs. It suggests that IGF1 may be involved in triggering the expression peak of the tshβb paralog at smoltification, thus representing a potential internal signal in the link between body growth and smoltification metamorphosis.